2005
DOI: 10.1074/jbc.m509164200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-mediated Neurite Outgrowth Is Differently Regulated between Cortical and Hippocampal Neurons

Abstract: The acquisition of neuronal type-specific morphogenesis is a central feature of neuronal differentiation and has important consequences for region-specific nervous system functions. Here, we report that the cell type-specific cholesterol profile determines the differential modulation of axon and dendrite outgrowths in hippocampal and cerebral cortical neurons in culture. The extent of axon and dendrite outgrowths is greater and the polarity formation occurs earlier in cortical neurons than in hippocampal neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 30 publications
7
59
0
Order By: Relevance
“…Signaling differences in brain regions have been previously reported. For instance, differences in the cholesterol levels in the cortex and hippocampus are suggested to underlie greater outgrowth in cortical neurons than in hippocampal neurons (Ko et al, 2005), and we previously reported that the compartmentalization of Fyn underlies, at least in part, the differences in the actions of ethanol in the hippocampus versus the cortex (Yaka et al, 2003b). Some differences are also found between the dorsal and the ventral striatum.…”
Section: Discussionmentioning
confidence: 88%
“…Signaling differences in brain regions have been previously reported. For instance, differences in the cholesterol levels in the cortex and hippocampus are suggested to underlie greater outgrowth in cortical neurons than in hippocampal neurons (Ko et al, 2005), and we previously reported that the compartmentalization of Fyn underlies, at least in part, the differences in the actions of ethanol in the hippocampus versus the cortex (Yaka et al, 2003b). Some differences are also found between the dorsal and the ventral striatum.…”
Section: Discussionmentioning
confidence: 88%
“…Cholesterol, apart from being an essential component of cellular membranes, is a key regulator of cellular processes in the central nervous system (CNS), playing a role in promoting neurite outgrowth [1][2][3][4][5], in synaptogenesis and synaptic integrity, and in neurotransmitter release [6][7][8][9]. In addition to the brain-specific activities, cholesterol synthesis generates intermediate products, such as isoprenoids and ubiquinone [10].…”
Section: Introductionmentioning
confidence: 99%
“…This difference is also present in the detergent resistant membranes, suggesting that hippocampal neurons are also enriched in membrane rafts. Furthermore, the data suggest that cholesterol is a potent regulator of in vitro neuronal morphology: increased cholesterol levels lead to less complex dendritic arborization (Ko et al 2005). Support for this view also comes from an independent study by Pooler et al, in which they report that a Hmgcr inhibitor, pravastatin, enhanced neurite outgrowth, neurite length, and neurite branching in cultured hippocampal neurons (Pooler et al 2006).…”
Section: Regulation Of Cns Cholesterol Biosynthesis: a Novel Mechanismentioning
confidence: 90%
“…Considering the complexity of adult nervous system, it is not surprising that different brain regions show marked differences in cholesterol content (Zhang et al 1996). In particular, hippocampal and cortical neurons show different intrinsic concentrations of cholesterol (Ko et al 2005). This difference is also present in the detergent resistant membranes, suggesting that hippocampal neurons are also enriched in membrane rafts.…”
Section: Regulation Of Cns Cholesterol Biosynthesis: a Novel Mechanismentioning
confidence: 99%